Saúde mental e cuidado de adolescentes residentes do meio rural - Soster, Francieli Franco (2024)
Considering adolescents as individuals who are part of a historical process and embedded in a specific social context, it is necessary to understand the particularities that encompass their health. This study is a descriptive and exploratory qualitative research aimed at identifying the health needs and care demands of adolescents attending rural schools. Data collection took place from April to October 2023 in seven municipal elementary schools in the municipality of Palmeira das Missões, through semi-structured interviews. The participants were 27 adolescents aged between 10 and under 19 years, residing in the municipality's rural area and enrolled in one of the participating schools. After data collection, the interviews were fully transcribed and subjected to inductive thematic analysis. From the analysis, two categories emerged: “Mental health demands of adolescents in rural schools” and “Family care demands for adolescents in rural schools.” The adolescents reported mental health demands related to anxiety, self-harm, suicide, psychological distress due to grief, bullying, and reduced leisure activities. They also mentioned care demands resulting from fragile family relationships, marked by experiences of parental abandonment and rejection, as well as fear and insecurity regarding family communication due to aggressive and authoritarian parental behaviors. It is concluded that rural adolescents participating in the study face complex and multifaceted challenges across various dimensions of their lives, with direct implications for their emotional, social, and psychological development. Therefore, this study highlights that integrated strategies between the health, education, and social assistance sectors such as those proposed by the Health in Schools Program (PSE) are essential to promote well-being and mitigate the impacts of these adversities. Furthermore, it suggests the development of extension and research activities specifically targeted at rural adolescents to meet their demands, promoting mental health, coping with school challenges, strengthening family bonds, and ensuring access to leisure and socialization opportunities.